NORMALISASI DRAINASE APRON B-C DI BANDAR UDARA HUSEIN SASTRANEGARA BANDUNG - Agie Santoso Margono,; Djoko Priambodo,; Oka Fatra, (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
Right now, Husein Sastranegara International Airport have a drainage problem, clogged frequent, flooded, and some parts of trails cover are damaged because it is age in Apron B-C Airside. Therefore have to repair it, them is drainage trails cover change, clean the sediment so there is no clogged anymore. In the to make the drainage system condition (2015 KP 39 or FAA AC 150_5320_5c). The daily rain maximum data obtained from BMKG rain station location in Husein Sastranegara International Airport for the total if 30 years. This rain data will processed of analysis top of flood debit. Meanwhile, the new drainage model using a closed channel using a box culvert precast with 90 x 90 x 9 dimension. To accommodate drainage channel inlet, will create an open channel segment which is in same time serves as man hole using u-ditch precast followed cover from hollow steel. This inlet or man hole are placed every 50 meter.